Obstructive Sleep Apnea Dynamically Increases Nocturnal Plasma Free Fatty Acids, Glucose, and Cortisol During Sleep - Chopra, Swati; Rathore, Aman; Younas, Haris; Pham, Luu V; Gu, Chenjuan; Beselman, Aleksandra; Kim, Il-Young; Wolfe, Robert R; Perin, Jamie; Polotsky, Vsevolod Y; Jun, Jonathan C (The journal of clinical endocrinology and metabolism, 2017)
ContextObstructive sleep apnea (OSA) is associated with diabetes and cardiovascular disease. This association may be related to metabolic changes that transpire during sleep in OSA.ObjectiveTo examine the impact of OSA, elicited by cessation of continuous positive airway pressure (CPAP), on frequently sampled nocturnal metabolic markers including plasma free fatty acids (FFAs), glucose, insulin, triglycerides (TGs), cortisol, and lactate, as well as glucose production, oral glucose tolerance, blood pressure (BP), endothelial function, cholesterol, and high-sensitivity C-reactive protein (hsCRP).Design and SettingRandomized crossover trial of CPAP vs CPAP withdrawal.PatientsThirty-one patients with moderate to severe OSA acclimated to CPAP.InterventionPatients underwent attended polysomnography while sleeping with therapeutic CPAP, or after CPAP withdrawal, in random order. Venous blood was sampled at ∼20-minute intervals on both nights. In 11 patients, we assessed glucose kinetics with an infusion of 6,6-[2H2]glucose.ResultsCPAP withdrawal caused recurrence of OSA associated with hypoxemia, sleep disruption, and heart rate (HR) elevation. CPAP withdrawal dynamically increased nocturnal FFA (P = 0.007), glucose (P = 0.028), and cortisol (P = 0.037), in proportion to respiratory event frequency, HR elevation, or sleep fragmentation. Diabetes predisposed to glucose elevation. CPAP withdrawal also increased systolic BP (P = 0.017) and augmentation index (P = 0.008), but did not affect insulin, TGs, glucose production, oral glucose tolerance, cholesterol, or hsCRP.ConclusionOSA recurrence during CPAP withdrawal increases FFA and glucose during sleep, associated with sympathetic and adrenocortical activation. Recurring exposure to these metabolic changes may foster diabetes and cardiovascular disease.We studied the overnight metabolic profile of patients during sleep, in the presence or absence of sleep apnea. Sleep apnea caused dynamic elevations of plasma FFA and glucose.